The relationship of body mass index, diet, and eating pattern with orthorexia nervosa amongst medical students - Adiningsih, Sri; Wilson, Wilson; Tejoyuwono, Agustina Arundina Triharja (Intelektual Pustaka Media Utama, 2024)
Orthorexia nervosa (ON) is an obsessive behavior towards healthy food with more importance on the quality than the quantity of food. Medical students tend to experience ON. The prevalence of ON in the Faculty of Medicine, University of Tanjungpura (FK UNTAN) is around 56.1%. The study is conducted to assess the relationship between body mass index (BMI), diet, and eating patterns with ON indications for students of the Medical Study Program, FK UNTAN. This study uses mixed method (quantitativequalitative), for 66 students (2020 and 2021 batches) through proportionate stratified sampling and 10 students with low and high ON indications with the convenience methode. Analysis used Spearman's rho correlation test and contingency coefficient; qualitative analysis used descriptive inductive method. Bivariate analysis showed p>0.005 for BMI (p=0.139, diet (p=0.105), and the results were invalid for dietary pattern. Qualitative analysis shows people with ON can be influenced by social media which is characterized by their habit of seeking inspiration for healthy eating behaviors. There is no statistically significant relationship between BMI, diet, and eating patterns with ON but still found in FK students because of their knowledge related to nutrition, health and the desire to avoid illness.